PERAN BPD (BADAN PERMUSYAWARATAN DESA ) DALAM PEMBENTUKAN KOPERASI MERAH PUTIH STUDI DI DESA PADEMAWU BARAT - Subakti, Try; Partiah, Siti (CV. Jendela Gagasan, 2025)
This Community Service aims to determine the duties of the Village Consultative Body in the formation of village cooperatives. The Village Consultative Body is part of the village government that has the task and authority to supervise the implementation of village government. One of the new programs based on the order of the central government is the formation of the Red and White Village Cooperative. This study uses an empirical research type with a sociological approach method because to obtain data must come directly either through participant observation or semi-structured interviews. The data used were observations during village deliberations in West Pamedawu, interviewing several Village Consultative Bodies there. In the formation of village cooperatives, the Village Consultative Body is tasked with holding village deliberations as the beginning of the formation of village cooperatives. In the village deliberation, there are several things discussed, including the name of the cooperative, type of business, village cooperative capital and also the flow of submission of the cooperative and in the preparation of the village cooperative management. The conclusion is that the Village Consultative Body still has an important role in the formation of village cooperatives because, in its formation, it must go through village deliberations where village deliberations are activities that are the responsibility of the BPD it self.